Skill transferability and mismatch among post-training graduates an application of the task-based approach - Generalao, Ian Nicole A.
This paper uses the task-based framework to examine the extent of skill transferability across occupations among Filipino post-training graduates using the graduate tracer study of Technical Education and Skills Development Authority (TESDA). From the task contents of occupations obtained from ISCO-08, a task portfolio for every occupation is constructed. Distance and direction measures are developed to classify an occupational move as up-skilling, down-skilling or a lateral move. The combination of these two measures estimates the level of skill mismatch associated with occupational mobility and the extent of human capital accumulation or loss in the process. Using maximum likelihood Heckman sample selection regressions, the study finds a significant positive relationship between occupational distances and wage changes supporting the model’s prediction of human capital accumulation associated with wage gains. To measure the transferability of skills in the labor market, this study applies the occupational distance measure to investigate the effectiveness of training programs in matching the expected and actual post-training occupations of graduates. We find that only a small portion among post-training graduates experience job-training match suggesting the poor performance of training programs in the aspect of job-training matching. Correlates of this job-training mismatch are computed using logit regressions. Finally, policy recommendations and areas of future study are presented.